SISTEM E-SKRIPSI FAKULTAS TEKNIK UNIVERSITAS PAHLAWAN TUANKU TAMBUSAI: Universitas Pahlawan Tuanku Tambusai, UPTT, Laravel Framework, E-Skripsi - Gusti Tri Prayoga; Novi Yona Sidratul Munti; Emon Azriadi (Universitas Pahlawan Tuanku Tambusai, 2022)
Tuanku Tambusai Hero University (UPTT) is one of the tertiary institutions in Riau Province, precisely located in Bangkinang District, Kampar Regency. Universitas Pahlawan Tuanku Tambusai is currently utilizing information on the role of thesis technology to make it easier for students to submit Web-based titles. The purpose of this research is to build an E-Thesis website for the Faculty of Engineering, Universitas Pahlawan Tuanku Tambusai to make it easier for students in submitting thesis titles and to make it easier for lecturers in terms of serving students. The method of this research is system analysis, design, programming, testing and implementation. Testing the E-Thesis website uses the Blackbox method, namely testing based on application functionality. With the construction of the E-Thesis Website, it is hoped that it will make it easier for students to submit titles at the Faculty of Engineering.